Motor development and assertivity in children who practice violin and football - Manrique Espitia, Judy Liliana; Hernández Espitia, Nairo Yesid; Flórez Villamizar, Jairo Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The aim of this paper is to determine the levels of motor development and assertiveness of children from 10 to 12 years old, of extracurricular programs of violin and soccer in Villa de Leyva, supported by a descriptive correlational design, with a quantitative approach, applying the CABS type II assertive behavior scale and the Psychomotor Battery (BPM), these instruments allow to find positive results in the participants of the two groups, by being classified as “good” in the psychomotor profile; in terms of passive and aggressive behavior, heterogeneity is evident and assertive behavior with similar averages of 18.65 and 18.85 is homogeneous. Finally, there is a significant moderate and direct correlation between the levels of motor development and assertiveness of the participants, confirming that the practice of extracurricular activities such as indoor soccer and violin significantly influence the integral development of the child.